Влияние некоторых органов чувств на дистантную ориентацию рыб - Абросимова, А.М.; Васина, С.Г.; Гуменюк, С.Б. (Вестник зоологии, 1971)
The experiments on determining the effect of some sense organs of sight, smell and
lateral line — on fish orientation showed that only complex isolation of all the abovementioned sense organs in Rutilus rutilus (L.), Blicca bjoerkna (L ), Abramis ballerus
(L.), Esox lucius L., Perca fluviatilis L. disturbs the orientation and cause s disorderly
movement. The isolation of some sense organs in the fish under experiment has no effect
on the choice of direction, exept for Esox lucius L., in which the disturbance in smell organ somewhat change s the orientation.